2020
DOI: 10.31932/ve.v11i2.829
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Komik Digital Pada Materi Gerak

Abstract: ABSTRAKPerkembangan teknologi digital dewasa ini telah terjadi secara masif tidak terkecuali di dunia pendidikan Mengingat pesatnya perkembangan teknologi digital maka penelitian ini berupa pengembangan bahan ajar komik digital pada materi gerak. Tujuan penelitian ini adalah untuk mengembangkan bahan ajar komik digital pada materi gerak sebagai pendukung dalam pembelajaran. Metode yang digunakan dalam penelitian ini adalah metode penelitian dan pengembangan (research and development). Rancangan penelitian yang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
1
11
0
10
Order By: Relevance
“…Kemajuan zaman di bidang ilmu teknologi semakin berkembang (Azizul et al, 2020;Lestari, 2018). Teknologi yang sangat populer di era globalisasi ini adalah gadget (Dewi, 2019;Patricia, 2020).…”
Section: Pendahuluanunclassified
“…Kemajuan zaman di bidang ilmu teknologi semakin berkembang (Azizul et al, 2020;Lestari, 2018). Teknologi yang sangat populer di era globalisasi ini adalah gadget (Dewi, 2019;Patricia, 2020).…”
Section: Pendahuluanunclassified
“…Other studies are not much different. (Andayani et al, 2020;Azizul et al, 2020;Harmawati et al, 2020;Kurniawati & Koeswanti, 2021;Ratnasari & Ginanjar, 2020;Sukmanasa et al, 2017) It also showed that the development of digital comics gets good to very good qualifications with high scores. The results obtained are related to the characteristics of the comic itself, which is the arrangement of ordered pictures and storytelling, which is an interesting thing for elementary school students.…”
Section: Discussionmentioning
confidence: 94%
“…The development of digital comic learning media to improve student learning achievement in elementary schools results from the validity of the material expert of 84% with the very high category and the validity of the media expert of 77% with the high category (Kurniawati & Koeswanti, 2021). Development of comics for motion teaching materials with the percentage of validity of material experts 76.89% with a decent category and media experts with 89.17% with a very good category (Azizul et al, 2020). The development of digital-based comic media towards students' critical thinking skills on metamorphosis material in high class is very well qualified from the validity test of material experts and practitioners (Andayani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Teknologi adalah benda-benda atau alat-alat yang diciptakan oleh menusia untuk membantu dan mempermudah pekerjaan manusia dalam melakukan beberapa hal (Husaini, 2019;Saputri & Pambudi, 2018). Semakin berkembangnya teknologi dan informasi membuat semua orang semakin mudah mengakses segala macam informasi (Azizul, Riski, Fitriyani, & Sari, 2020;Lestari, 2018). Salah satu wujud dari perkembangan teknologi adalah dengan adanya gadget (E. Dewi, 2019;Patricia, 2020).…”
Section: Pendahuluanunclassified